(3GdLhgQI GdNGdUI Yf GdThGFH aj GdYbGFO GdeJbheI Ydi LejY GdePGgH GdJi SCd YfgG YHO GdMb YHO GdMejOs - (3TeS GdOjf YHO GdUeO Hf YHO Gddg GdYdhj GdOGeZGfj,J (B967 (3g` s
(3ChdgG (B:s
(3jHOC HGdaUd GdChd ai HjGf eG fbe Ydi cd aQbI s
(3BNQgG (B:s
(3jfJgi HMOjKI (B( (3hEPG CQOJ Cf JbdO GMO GdTjYI (B) s
(3HgG fXGe GdJYbjHIs
(3hbO CJe GdeDda cJGHJg SfI (B967(3g`s
(3bQf GdfSN (B:s
(3GdbQf GdQGHY YTQs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B10s
Keywords: (3CUhd Gdabgs